Esterolytic and lipolytic activities of lactic acid bacteria isolated from ewe's milk and cheese - Katz, Marta (2002)
In the present work, we report on the esterase and lipase activities of lactic acid bacteria representing the genera Lactococcus, Leuconostoc, Lactobacillus, and Enterococcus isolated from ewe’s milk and cheeses. Esterase activity was studied using a- and b-naphthyl derivatives of 2 to 12 carbon atoms and postelectrophoretic detection. The lactic acid bacteria evaluated had intracellular esterase activities, which preferentially degraded the a- and b-naphthyl derivatives of 2 to 6 carbon atoms. By studying postelectrophoretic patterns, it was found that some strains presented more than one esterase. Lactobacillus plantarum O236 showed four enzymes that hydrolyze carboxyl ester linkages with different speci city. Lipase activity was studied in intracellular and extracellular fractions using tributyrin, tricaprylin, triolein, and milk fat as substrates. The intracellular and extracellular fractions of Leuconostoc mesenteroides O257, Lactobacillus plantarum O236, and Lactobacillus acidophilus O177 were able to hydrolyze tributyrin. L. plantarum O186, L. acidophilus O252, Enterococcus faecium O174 and O426, and Enterococcus faecalis Ov409 showed lipase activity associated with the intracellular fraction on tributyrin. Lactococcus lactis O233, L. plantarum O155, and Lactobacillus casei O190 did not hydrolyze triglycerides. Not all strains that showed esterase activity exhibited high activity on triglycerides. Esterase and lipase activities were species- and strainspeci c. Wide variations in activity between strains highlight the need for selecting appropriate starters to produce enzyme-modified cheese as well as accelerated ripened cheese.